Depression, anxiety and associated factors among infertile women in Zanzibar - Wenxuan Gao; Yuxin Ju; Lingling Gao; Hassanat Mohammed Abdalla; Sabra Salum Masoud (Journal of Psychosomatic Obstetrics and Gynecology)
To determine the prevalence of depression and anxiety among infertile women in Zanzibar and explore their risk factors, infertile female patients were recruited from Mnazi Mmoja Hospital in Zanzibar. The questionnaire survey was adopted. Ordinal univariate and multivariate logistic regression analyses were separately conducted to identify the risk factors associated with depression and anxiety in this sample. Among 330 infertile women, the overall prevalence of depression among patients with infertility was 40.3% and the incidence of anxiety was 66.06%. Older age (odds ratios (ORs): 1.056, 95%CI: 1.004–1.112, p = .035) and low education level (OR: 0.685, 95%CI: 0.475–0.987, p = .042) were the independent risk factors for depression. Low educational level (OR: 0.678, 95%CI: 0.482–0.954, p = .026) and primary infertility (OR: 1.546; 95%CI: 1.028–2.324, p = .036) were the risk factors for anxiety. Low educational level is a risk factor for both depression and anxiety in infertile women. Older age is a risk factor for depression and primary infertility is a risk factor for anxiety.